Using an Early Warning Score for Nurse Shift Patient Handover: Before-and-after Study - Jee-In Hwang; Sung Wan Kim (Elsevier, 2022)
Purpose: This study aimed to examine the impact of using an early warning score for shift patient handover on nurse and patient outcomes. Methods: A before-and-after study was conducted with nurses and patients in three general wards in a tertiary teaching hospital. A short-time nurse education on the National Early Warning Score 2 and the use of a checklist for score calculation were performed from June 4, 2019 to June 30, 2019. Outcomes of nurse response (safety competency, handover quality, teamwork, safety climate, and documentation of vital signs and clinical concerns), patient response (deterioration occurrence postadmission, hospitalization length, and discharge status), and adverse events (mortality, cardiopulmonary arrest, and unplanned intensive care unit admission) were measured using questionnaires and medical record reviews. Data from 89 nurses and 388 patients were analyzed. Results: Regarding nurse outcomes, handover quality (p < .001), teamwork (p = .004), safety climate (p = .018), and recordings of vital signs (p = .047) and clinical concerns (p = .008) increased after early warning score use. However, no significant change in the safety competency scores was observed. Regarding patient outcomes, there were no significant changes in the occurrence of deterioration, hospitalization length, discharge status, and occurrence of adverse events between preintervention and postintervention. Conclusion: Despite no significant changes in patient outcomes, using a simple, evidence-based early warning score for patient handover enhanced socio-cultural factors for patient safety, with improved patient monitoring. The findings provide evidence that supports the active implementation of an early warning score to improve patient safety.